Noise Induced Hearing Loss in Steel Factory Workers - Agarwal, Gaurav; Nagpure, Prakash S.; Gadge, Shweta V. (International Journal of Occupational Safety and Health, 2016)
Background: Industrial noise is usually considered mainly from the point of view of environmental health and safety, rather than nuisance, as sustained exposure can cause permanent hearing damage. Objective: To assess the Noise induced hearing loss in steel factory workers. Methods: It was a cross sectional study done to evaluate the hearing status of factory workers, working nearby a rural hospital, which were then correlated with the duration of work and SPL (in dBA) of exposure at their workplace. Results: In this study, Noise Induced Hearing Loss (NIHL) was calculated in the workers by taking the average of the 4 frequencies i.e. 500Hz, 1000Hz, 2000Hz and 4000Hz in right and left ear separately. Results showed that 129 (37.83%) workers were having Mild SNHL in Right ear i.e. between 26- 40 dB. 203 (59.54%) of the workers were having normal hearing i.e. hearing loss not exceeding 25 dB. Only 9 (2.63%) workers had moderate (41-60 dB) hearing loss in right ears. Whereas in case of left ears results showed that 145 (42.52%) workers were having Mild SNHL in left ear i.e. between 26- 40 dB. 185 (54.25%) of the workers were having normal hearing i.e. hearing loss not exceeding 25 dB. Only 11 (3.23%) workers had moderate (41-60 dB) hearing loss. Conclusion: Duration of exposure of individuals was found in the range from 6 years to 20 years. Maximum number of workers i.e. 235 (68.92%) were exposed to a time duration of 16 to 20 years followed by 96 (28.15%) who were exposed to 11-15 years. There were 10 (2.93) workers who were having the exposure of 6 to 10 years. International Journal of Occupational Safety and Health, Vol 4 No 2(2015) 34 – 43